The Advent of Islam in Bengal; An Economic Perspective - Islam, Md Thowhidul (IIUC Studies, 2012)
This article aims at examining the causes to the advent of Islam in Bengal with a view to identify the economic perspectives in particular. Islam took about six hundred years for its advent into Bengal with political conquest by Bakhtiyar Khalji in the early 13th century, while it had come to Arabia at the beginning of the 7th century. But long before the conquest of Bengal by Bakhtiyar Khalji, the Arab traders had established commercial relation with the coastal lands of Bengal. Islam began to enter into Bengal with the hands of these early Arab Muslim traders. With the beginning of this early advent, Islam started to enter into Bengal through both the sea and land routes on different circumstances. Though there were many other reasons and grounds for the advent of Islam in Bengal, but the economic perspectives were the foremost and forerunner of the causes. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12262 IIUC Studies Vol.7 2011: 91-106